Rural vulnerability and institutional dynamics in the context of COVID-19: A scoping review - John, Sokfa F.; Okem, Andrew Emmanuel; Mubangizi, Betty Claire; Adekanla, Niyi; Ngubane, Londeka P.; Barry, Ibrahim (AOSIS, 2022)
This study reviewed the impact of the coronavirus disease 2019 (COVID-19) on pre-existing vulnerabilities in rural communities using the scoping review strategy. It focused on manuscripts published on the topic in 2020. Based on 39 studies that met our inclusion criteria (out of 507 studies), we note that COVID-19 is exacerbating pre-existing rural vulnerabilities, including poverty, remoteness, socio-economic marginalisation and high unemployment. There is limited evidence that rural communities are resilient to the pandemic. Reduction in household expenditures and the community food system are the only reported forms of resilience. Although local institutions are supporting rural communities in responding to the impacts of the pandemic, several institutional dynamics undermine the effectiveness of the response. The increased risk of the pandemic is likely to reduce incomes and standards of living amongst poor communities. Thus, coping strategies were identified such as starting small gardens in communities, diet changes, targeting community markets with produce rather than retailers and food swap using social media, with food swap being the most adopted coping strategy. Although this study does not offer a comprehensive picture of the levels and nature of vulnerability, resilience and institutional dynamics of rural communities in different parts of the world reveal the limitations of existing knowledge of the vulnerability of rural communities in the context of COVID-19. This underscores the importance of further studies on rural vulnerability in the context of COVID-19 that will enable evidence-based responses to the pandemic in rural contexts.
Keywords: vulnerability; rural; resilience; livelihoods; COVID-19; adaptive capacity